2014
DOI: 10.1186/1755-7682-7-31
|View full text |Cite
|
Sign up to set email alerts
|

Changes in full blood count parameters in leptospirosis: a prospective study

Abstract: BackgroundLeptospirosis presents diagnostic challenges to clinicians, in settings where other acute febrile illness are prevalent. The patterns of serial changes in haematological parameters in leptospirosis has not been evaluated previously.MethodsClinical and laboratory data were collected prospectively from patients with leptospirosis in two hospitals in Sri Lanka. Leptospirosis was diagnosed based on WHO clinical criteria with confirmation using Microscopic Agglutination Test titre > 400 or 4 fold rise bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 5 publications
3
30
1
1
Order By: Relevance
“…promoted the formation of mixed platelet–neutrophil aggregates. Thrombocytopenia is a common feature of leptospirosis, but its origin is still not clear (Adiga, Mittal, Venugopal, & Mittal, ; de Silva et al, ; Goeijenbier et al, ; Raffray et al, ; Tunjungputri et al, ). In this regard, the formation of circulating mixed aggregates could represent a possible mechanism that accounts for the clearance of platelets and the consequent thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…promoted the formation of mixed platelet–neutrophil aggregates. Thrombocytopenia is a common feature of leptospirosis, but its origin is still not clear (Adiga, Mittal, Venugopal, & Mittal, ; de Silva et al, ; Goeijenbier et al, ; Raffray et al, ; Tunjungputri et al, ). In this regard, the formation of circulating mixed aggregates could represent a possible mechanism that accounts for the clearance of platelets and the consequent thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is upregulated not only in response to a variety of signals, including bacterial components, but also by IL-1β and other cytokines, suggesting a complex activation network (Moon et al, 2000;Tuyt et al, 1999). Moreover, acting synergistically, they could also be responsible for the neutrophilia (Chiba et al, 2017) observed during acute leptospirosis in humans (de Silva et al, 2014;Lindow et al, 2016;Raffray et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Thrombocytopenia is observed in approximately 75% of patients at day five of illness. In tropical regions, this can provide further diagnostic uncertainty in the undifferentiated febrile patient, in that it can mimic arboviruses such as dengue fever . A marked lymphopenia represents a common early finding yet a decreased total white cell as demonstrated as in this case is unusual.…”
Section: Discussionmentioning
confidence: 76%
“…26 Neutrophilia and low haemoglobin predicted severe disease in this study. Mortality was 50% in patients with total leucocyte count of 4000-11000/cmm and 41.6% in those with total leucocyte count of >11,000/cmm.…”
Section: Leptospirosismentioning
confidence: 90%